Evolutionary Relationships and Functional Diversity of Plant Sulfate Transporters - Takahashi, Hideki; Buchner, Peter; Yoshimoto, Naoko; Hawkesford, Malcolm J.; Shiu, Shin-Han (Frontiers in Plant Science, 2012)
Sulfate is an essential nutrient cycled in nature. Ion transporters that specifically facilitate the transport of sulfate across the membranes are found ubiquitously in living organisms. The phylogenetic analysis of known sulfate transporters and their homologous proteins from eukaryotic organisms indicate two evolutionarily distinct groups of sulfate transport systems. One major group named Tribe 1 represents yeast and fungal SUL, plant SULTR, and animal SLC26 families. The evolutionary origin of SULTR family members in land plants and green algae is suggested to be common with yeast and fungal SUL and animal anion exchangers (SLC26). The lineage of plant SULTR family is expanded into four subfamilies (SULTR1–SULTR4) in land plant species. By contrast, the putative SULTR homologs from Chlorophyte green algae are in two separate lineages; one with the subfamily of plant tonoplast-localized sulfate transporters (SULTR4), and the other diverged before the appearance of lineages for SUL, SULTR, and SLC26. There also was a group of yet undefined members of putative sulfate transporters in yeast and fungi divergent from these major lineages in Tribe 1. The other distinct group is Tribe 2, primarily composed of animal sodium-dependent sulfate/carboxylate transporters (SLC13) and plant tonoplast-localized dicarboxylate transporters (TDT). The putative sulfur-sensing protein (SAC1) and SAC1-like transporters (SLT) of Chlorophyte green algae, bryophyte, and lycophyte show low degrees of sequence similarities with SLC13 and TDT. However, the phylogenetic relationship between SAC1/SLT and the other two families, SLC13 and TDT in Tribe 2, is not clearly supported. In addition, the SAC1/SLT family is absent in the angiosperm species analyzed. The present study suggests distinct evolutionary trajectories of sulfate transport systems for land plants and green algae.